Human Fetal Development And The Ways Of Asthabrata As An Idea In The Creation Of Sinjang Batik Tulis - Danang Priyanto; FP Sri Wuryani (Universitas Indraprasta PGRI, 2019)
Human beings which are wired as leaders should live based on the practice of transcendent value and total clarity on noble deeds. It functions as a guideline in living to avoid the crisis of morality that often occurs today. One of the values in this leadershipquality is the teaching of asthabrata containing the noble deeds of a leader who symbolized in the elements of the universe: the fire, the ground, the water, the air, the moon, the clouds, the sun, and the stars. The stage of human fetal development occurs from the age of one to nine months. These stages, along with the teachings of asthabrata become the base of an idea in the creation of batik art. The idea comes from the question of how to process the development stages of human fetal and ways of asthabrata as a base on creating the batik artwork which conveys sublime values about leadership. The purpose of this batik artwork creation are:incorporating the concept of human fetal development as part of human life cycle with the tradition of batik; Conveying the sublime sublime of leadership based on the asthabrata which refers to human nature as a natural born leader. The creation processcovering the method of design exploration, design process, and batik as a result of design by establishing the combination ofhuman fetal development and the asthabrata. The result shows nine sinjang batik tulis artworks, covering; Hamasesa Tan Pilih Warna (manage without seeing the color), Sukci (sacred), Hanguripi Sagung Dumadi (give strength to all life), Girise Kang Samya Miyat (be who you want to see), Sorota Hayem Angayomi (make peaceful and full protection), Jembar Tanpa Pagut(sincerity without limit), Muntir Tan Ana Pedhote (infinite rotation), Panengeraning Keblad (signpost), and Ngudi Kasampurnan(sharpening perfection).